The Oxford Handbook of Genocide Studies. - Bloxham, Donald.
1 online resource (690 pages)
Keywords: The first book to subject both genocide and this young discipline to systematic, in-depth analysis. Thirty-four renowned experts study genocide world-wide through the ages by taking regional, thematic, and disciplinary approaches.